Genital premalignant and malignant diseases: a retrospective study of male genital skin biopsies. (27th February 2021) - Mazzoni, Daniel; Winkle, David; Pool, Louis; Hall, Anthony; Muir, Jim
Abstract: Background: Genital skin malignancies are a rare entity encountered by clinicians that may result in significant morbidity and mortality. Lack of familiarity or expertise in this area among clinicians can delay appropriate management of these conditions and may result in disease progression. Methods: We performed a retrospective descriptive cohort study of male patients who received a genital skin biopsy reported by one major dermatopathology laboratory between January 2017 and December 2018 with a histological diagnosis of a premalignant or malignant condition. Patient age, type of clinician, clinical notes, genital site, type of biopsy performed, and histopathological diagnosis were evaluated. Results: Of the 1525 male genital skin biopsies available for analysis, 5% (74/1525) were premalignant or malignant diseases. These included penile intraepithelial neoplasia (PeIN) (42/74, 57%), followed by invasive squamous cell carcinoma (SCC) (11/74, 15%), Bowenoid papulosis (BP) (9/74, 12%), basal cell carcinoma (8/74, 11%), malignant melanoma (2/74, 2.7%), extramammary Paget's (1/74, 1.4%), and metastatic cutaneous deposits (1/74, 1.4%). PeIN and BP most commonly affected the penile shaft ([18/42] 43% and [4/9] 44%, respectively), invasive SCCs most commonly affected the glans penis (4/11, 36%), and all BCCs (8/8, 100%) were located on the scrotum. Invasive SCCs were most biopsied by urologists, BP was most biopsied by dermatologists, and PeINs and BCCs were most biopsied by general practitioners. Conclusions: A variety of genital malignancy types were found in males. A greater understanding of male genital premalignant and malignant conditions may help guide education and further research in this area.